1971
DOI: 10.1002/prac.19713130116
|View full text |Cite
|
Sign up to set email alerts
|

Zum Mechanismus der Oxydation mit Permanganat in alkalischer Lösung. II Oxydation tertiärer CH‐Bindungen

Abstract: Der Mechanismus der alkalischen Permanganatoxydation primärer und sekundärer C‐H‐Bindungen wurde unter der Annahme erklärt, daß das vorgelagerte Gleichgewicht des alkalischen Permanganatzerfalls wirksam wird: In einer Folgereaktion reagieren die OH‐Radikale mit dem organischen Substrat. Diese Annahme wird gestützt durch das Geschwindigkeitsgesetz, 18O‐Traceruntersuchungen, durch die Größe des kinetischen Isotopieeffektes und das Vorhandensein eines inversen Solventisotopieeffektes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It has been suggested 1~ that pathway A of reaction (28), which involves the transfer of an H atom of the toluene methyl group on oxygen of the MnO 4-anion, is valid only for toluene solutions, whereas in aqueous solutions, oxidation involves hydride transfer: AH/A D ratios are due to the compensation effects for the KIE; when the structure of the reagent changes, systems with high and low KIE are described by a common compensation dependence.…”
Section: Ring Destructionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested 1~ that pathway A of reaction (28), which involves the transfer of an H atom of the toluene methyl group on oxygen of the MnO 4-anion, is valid only for toluene solutions, whereas in aqueous solutions, oxidation involves hydride transfer: AH/A D ratios are due to the compensation effects for the KIE; when the structure of the reagent changes, systems with high and low KIE are described by a common compensation dependence.…”
Section: Ring Destructionmentioning
confidence: 97%
“…Depending on the type of the transition state (TS) in the slow step of the reaction, the mechanism of electrophilic aromatic substitution including the successive formation of CTC (or radical ion pair) G and o-c0mplex H (see reactions (28), pathway" B) can be realized as three variants.…”
Section: Ring Destructionmentioning
confidence: 99%
“…It should be noted that it is spin allowed for two diamagnetic to react and form a singlet radical pair as in equation-5. Examples of hydrogen atom transfer between closed shell organic molecules have been described by Ruchardt and others [63,64,65] [56,57] in part because a recent pulse radiolysis study provided a new value for the pK a of HMnO 4 [68,74,75] The constant C is calculated as 57 ± 2 kcal/mol [69,70,71,72,78], with the common assumption that the entropies of MnO 4 and HMnO 4 are equal [70,71,72] a value of 80 ± 3 kcal/mol for the H-OMnO 3 bond strength is obtained. Alternatively the constant is not needed if relative bond are calculated from a thermodynamic cycle where hydrogen atom is transferred from another species.…”
Section: Discussionmentioning
confidence: 99%
“…Heckner and co-workers 37 concluded, from the rate law, kinetic deuterium isotope effects, 180-tracer experiments, and inverse solvent isotope effects, that the mechanism of the alkaline permanganate ion oxidation of pr/mary and secondary carbon-hydrogen bonds involves hydroxyl radicals [37][38][39] The kinetics and mechanism of the oxidation of tertiary hydrogen to hydroxyl by permanganate ion in alkaline solution have received some study. Kenyon and Symons 4° observed that systems of the type RR1CH(CH2)2COOH are oxidized to RR 1 COH(CH2)2COOH in 60-90% yields by alkaline manganate or permanganate ion.…”
Section: Carbon-hydrogen Single Bonds 34-' :18mentioning
confidence: 99%